Importance of public health tools in emerging infectious diseases. (1st December 2021) - Tang, Jin-Ling; Li, Li-Ming
Abstract : Jin-Ling Tang and Li-Ming Li argue that despite the lure of vaccines and new drugs, established public health measures will remain our best tool to control covid-19 and future epidemics